STUDI ATAS KINERJA BUMN SETELAH PRIVATISASI - Sri Lestari Kurniawati; Wiwik Lestari (University of Merdeka Malang, 2008)
This paper examined the post-privatization both of financial and market performanceof State-owned company (BUMN). The findings indicated that there was no significant increasein financial performance after privatization. All variables tested were statistically the samebetween before and after privatization. However, market performance showed significantresult in cumulative abnormal in 6th month. It meant that, investing in BUMN could give asignificant return after investing at least six months.